The Relationship Between Pregnant Women’s Level of Knowledge Regarding Iron (Fe) Tablet Consumption and the Incidence of Anemia - Yustina Oktarida (CV. AFDIFAL MAJU BERKAH, 2026)
Anemia among pregnant women remains a public health problem in Indonesia because it increases the risk of pregnancy complications as well as maternal and infant mortality. Low adherence to iron (Fe) tablet consumption is often associated with a low level of knowledge. This study aimed to determine the relationship between pregnant women’s level of knowledge regarding iron (Fe) tablet consumption and the incidence of anemia in the working area of Tanjung Agung Public Health Center, Ogan Komering Ulu Regency, in 2025. This study employed an analytical design with a cross-sectional approach involving 65 respondents selected using accidental sampling. Data were collected through interviews using a knowledge-level questionnaire and hemoglobin measurement using an Hb stick, then analyzed using the Chi-Square (χ²) test at a 95% confidence level. The results showed that 35 pregnant women (53.8%) experienced anemia, while 30 women (46.2%) were not anemic, with a p-value of 0.031, indicating a statistically significant relationship between pregnant women’s level of knowledge and the incidence of anemia. In conclusion, better knowledge among pregnant women regarding iron (Fe) tablet consumption is associated with a lower risk of anemia. It is recommended that health workers enhance nutrition education and conduct routine monitoring of adherence to iron tablet consumption at every antenatal care visit